Market Driven Strategi Tokopedia: Peran Kinerja pemasaran memediasi pengaruh Orientasi Pasar terhadap Keunggulan Bersaing - Ahmad Gunawan; Ratih Hurriyati; Puspo Dewi Dirgantari (ITB AAS INDONESIA, 2023)
Market-driven strategies contribute to the segmentation of the target market and determine positions against alternatives to build a company's competitive advantage. Strategic market segmentation is used by many companies to understand how customers' needs and the desire that vary to design effective marketing strategies. In addition, the application of grouping and predictive modeling provides an understanding to project managers to create loyalty or advanced programs that require a more specific approach to specific customers. This research aims to reveal the influence of market orientation on marketing performance, marketing performance on competitive advantage, market orientation to competitive advantage and the role of marketing performance mediating the influence of market orientation on competitive advantage. The data was collected through interviews and questionnaires. Hypotheses are tested with path analysis techniques and Sobel tests. The results of hypothesis testing show that all the suggested hypotheses are accepted. Market orientation has a positive and significant effect on marketing performance, market orientation has a positive and significant effect on competitive advantage, marketing performance has a positive and significant effect on competitive advantage and marketing performance is able to mediate the influence of market orientation on competitive advantage.